Consuming abjection: an examination of death and disgust in the black metal scene. Issue 2 (4th March 2018) - Podoshen, Jeffrey S.; Andrzejewski, Susan A.; Wallin, Jason; Venkatesh, Vivek
ABSTRACT: This paper examines abjection in the context of the extreme (black) metal scene. Moving beyond the ritual-heavy, community work that dominates much of the death-related consumption literature, our study pieces together death, violence, misanthropy, blood and social tensions to create novel insights into the consumption of disgust. Based on our interview and participant observation methodologies, we present work that explains how death-oriented consumption and abjection is manifested for some consumers and actually plays a role as an affront to mainstream orientations and the greater social order. Additionally, our work indicates that the use of abjection can be seen as a boundary and source of delineation between the "acceptable" and the "unacceptable" in society.